2007
DOI: 10.1590/s0103-84782007000200036
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação de codornas de postura com rações contendo levedura de cana-de-açúcar

Abstract: II Nádia de Melo (0, 3, 6, 9, 12, 15% de inclusão)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
1
2
0
10
Order By: Relevance
“…RR is an important physiological parameter for the characterization of the comfort/stress condition of animals (Santos et al, 2006). The values obtained in the present study are within the RR range considered as ideal for birds, which must be from 20 to 30 mov min -1 , with mean of 25 mov min -1 (Souza et al, 2005). However, the environment did not cause discomfort to the quails.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…RR is an important physiological parameter for the characterization of the comfort/stress condition of animals (Santos et al, 2006). The values obtained in the present study are within the RR range considered as ideal for birds, which must be from 20 to 30 mov min -1 , with mean of 25 mov min -1 (Souza et al, 2005). However, the environment did not cause discomfort to the quails.…”
Section: Resultssupporting
confidence: 65%
“…This is consistent with the literature, which reports that daily consumption by quails must be between 25 and 35 g d -1 . Sucupira et al (2007) observed mean consumption of 22.45 g d -1 , and this difference is justified by the difference in the diets used. One of the factors that can influence consumption is temperature, i.e., with the increase in air temperature, birds stop consuming feed and start using mechanisms to dissipate heat from the body to the environment.…”
Section: Resultsmentioning
confidence: 94%
“…No período de 16 a 34 semanas de idade de poedeiras, Ayanwale et al (2006) observaram que com a suplementação da levedura S. cerevisiae, nos níveis de 0,25; 0,50; 0,75 e 1%, na dieta o peso do ovo produzido pelas aves alimentadas com 0,75% foi superior. Em um experimento realizado com a suplementação de níveis de 3 a 15% da levedura S. cerevisiae na dieta de codornas, no período de 14 a 23 semanas de idade, Sucupira et al (2007) observaram que o peso do ovo aumentou linearmente com o acréscimo da levedura na dieta. Neste estudo, os ovos produzidos pelas aves que receberam a suplementação do extrato de levedura apresentaram peso equivalente ou mais elevado, isso pode ser atribuído à presença dos peptídeos neste hidrolisado protéico, pois estes, além de apresentarem maior digestibilidade (Grimble et al, 1986), atuam disponibilizando aminoácidos para a síntese protéica (Gardner, 1998).…”
Section: Resultsunclassified
“…Estes resultados corroboram com os de Silva et al (2007). A ausência de variação significativa entre os tratamentos para peso da gema e do albúmen também estão de acordo com os resultados observados por Sucupira et al (2007) que incluíram níveis variando de 3 a 15% da levedura S. cerevisiae na dieta basal de codornas, no período de 14 a 23 semanas de idade. Na avaliação da suplementação da levedura S. Cerevisiae em cinco níveis (0; 0,25; 0,50; 0,75 e 1%), Ayanwale et al (2006) observaram que o peso da gema do ovo produzido por poedeiras, no período de 16 a 34 semanas de idade, foi significativo, sendo que com a suplementação de 0,75% da levedura o peso da gema foi superior.…”
Section: Resultsunclassified
“…It is also an essential component of several metalloenzymes (Macdowell, 1992;Vasquez et al, 2001;Ortolani, 2002;Marques et al, 2003). Moraes et al, (1999) and Sucupira et al, (2007) reported that the most common deficiencies of trace elements in sheep and cattle in Brazil were related to the deficit in copper and cobalt. The role and importance of copper in animal metabolism are well known (Vasquez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%